An experimental approach to assess the rock weathering and its implications on carbon mineralisation and metal behavior - Prasanna Mohan Viswanathan; Chidambaram Sabarathinam; Zuhairah Imanina binti Mohd Zuhaimi (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Reproducible statistical inference for assessing water quality: A decision framework for method selection and reporting - Bedour Alsabti; Todd Robinson; Chidambaram Sabarathinam; Prasanna Mohan Viswanathan; Domenik Wolff-Boenisch (Groundwater for Sustainable Development, 2026)

Distribution and partitioning of metals in surface sediments of a coastal river dominated ecosystem: Insights to geochemical fractionation, sources and ecological risk - Fiona Bassy William; Prasanna Mohan Viswanathan; Nagarajan Ramasamy; Chidambaram Sabarathinam; Vetrimurugan Elumalai (Marine Environmental Research, 2026)

Sources, spatial distribution and risk assessment of metals in tropical estuarine and coastal sediments - Anshuman Mishra; Prasanna Mohan Viswanathan; Chidambaram Sabarathinam; Sivakumar Karthikeyan (Marine Pollution Bulletin, 2026)

Metal enrichment in the tropical estuarine environment and associated health risk assessment using PMF and Monte Carlo simulation - Rakesh Roshan Gantayat; Prasanna Mohan Viswanathan; Nagarajan Ramasamy; Vetrimurugan Elumalai; Chidambaram Sabarathinam (Marine Environmental Research, 2026)

A comprehensive analysis of tracing the sources and dynamics of pollutants in a tropical Miri River, NW Borneo - Fiona Bassy William; Prasanna Mohan Viswanathan; Nagarajan Ramasamy; Chidambaram Sabarathinam (Sustainable Water Resources Management, 2025)
The fractionation and distribution of elemental composition in water (particulate and colloid) and sediments were assessed to understand the major geochemical processes that control the contaminant transport in the Miri River, NW Borneo. Further, the study also focused on determining the potential sources of geochemical elements and assessing the ecological risk. In this regard, 11 surface water and 35 river bed sediment samples were collected along the course of the Miri River and analyzed for various elemental compositions. Pollution indices such as geo-accumulation index (I geo ) and contamination factor (CF) were used to determine the pollution status of the river. Principal component analysis (PCA) was also used to identify the key geochemical processes that control the metal distribution and its sources. The interpretation of the results indicates that elemental distribution in size fractions showed an increasing concentration trend from the colloidal to the particulate fraction. Fe was observed to be the dominant metal in both water and sediments, indicating the weathering of river sediments. Cd, Pb and Zn are mostly derived from anthropogenic impacts and risk evaluation indicate the probability of adverse ecological threats to the riverine biota. Colloidal fractions (0.30 µm and 0.20 µm) were identified as the primary facilitators of contaminant transport, particularly in the upstream and midstream, whereas particulate (0.45 µm) dominates in the downstream due to the tidal influx of seawater. PCA analysis confirmed that the majority of pollutants were contributed by domestic and industrial discharge, seawater incursion, geogenic sources and agricultural inputs.

A spatio-temporal assessment of seawater quality in Miri-Sibuti Coral Reef: Evaluating for metal pollution, sources and dynamics - Sun Veer Moollye; Prasanna Mohan Viswanathan; Nagarajan Ramasamy; Anshuman Mishra; Chidambaram Sabarathinam; Chua Han Bing (Regional Studies in Marine Science, 2024)

Infusing genetic variability for productivity and drought tolerance traits from Brassica carinata into Brassica juncea genotypes - Omkar Maharudra Limbalkar; Prashant Vasisth; Rajendra Singh; Mahesh Rao; Guman Singh; Lal Singh; Gokulan Dhanasekaran; Manish Kumar; Mohan Lal Meena; Nanjundan Joghee; Chiter Mal Parihar; Viswanathan Chinnusamy; et al. (Genetic Resources and Crop Evolution, 2024)

Baseline survey of environmental parameters, radiation, and drip water hydrochemistry in Niah Caves (Sarawak, Malaysia) - Prasanna Mohan Viswanathan; Dominique Dodge-Wan (Environmental Monitoring and Assessment, 2024)
Relict caves in fenglin karst may typically have numerous entrances and openings. Hence, they host a variety of environments in which parameters such as light, airflow, humidity, and temperature may vary significantly over short distances. Similarly, drip water hydrochemistry, including isotopic values, may vary due to different contributions of various sources and residence time in the karst. This study investigated environmental parameters, including radiation, using hand-held instruments, along a transect within several major caves in the Niah karst of Sarawak (Malaysia). This has led to a baseline data set which showed an inverse relationship between humidity and temperature, gamma radiation levels that are about 25% of that in surrounding non-karst region, and high percentages of twilight zones in the studied caves. Airflow was found to be variable, with high values of 530 m 3 /s in Painted Cave and 122 m 2 /s in parts of Gan Kira passage, with flow towards the southeast at the time of the study. The hydrochemistry of the drip water and surface water was also analyzed and found to be dominantly Ca–Mg–Cl water type which indicates dissolution of minerals through water–rock interaction. In addition, the cave environment, particularly air temperature, humidity, and ventilation, also influences the drip water composition and isotopic values. Three different origins (precipitation, evaporation, and paleo-recharge) of drip water have been identified through the δ 18 O- δ 2 H diagram. Enriched isotopic values were observed in the cave entrance due to increased evaporation caused by lower humidity and higher air temperature. Factor analysis identifies the key geochemical processes responsible for the drip water chemistry. The outcome of this study provides the first baseline environmental data for the Niah caves, which could support future initiatives for sustainable management of this famous archeological site in southeast Asia.

Assessment of microplastics in highland rock salts of Northern Borneo - Prasanna Mohan Viswanathan; Anshuman Mishra; Dayarnan Raj Singam; Jaithish John (Journal of Environmental Management, 2024)

Distribution of natural radioactivity in different geological formations and their environmental risk assessment in Malaysia - Sheng Qin Seow; Prasanna Mohan Viswanathan; Dominique Dodge-Wan (Environmental Science and Pollution Research, 2024)
Labuan, Miri, Kundasang and Raub regions of Malaysia have very different geological formations and settings that could result in different levels of natural radioactivity. Hence, this study determines the influence of different geological formations on radioactivity in these locations using field measurements, petrology and geochemistry. A total of 141 gamma dose rates and 227 beta flux measurements were collected using Polimaster survey meters (PM1405) in these four regions. The gamma dose rate values range from 0.37 to 0.05 µSv/h with a mean value of 0.11 µSv/h. Beta flux values range from 3.46 to 0.12 CPS with a mean value of 0.57 CPS. Mineralogy and elemental composition of the different rock types were analysed using thin-section petrography, XRD, ICP and p XRF methods. Felsic igneous rocks such as syenite and granite have higher natural radioactivity and contain more radionuclide-bearing minerals such as apatite, zircon, allanite, K-feldspar, titanite, muscovite and biotite. Metamorphic rocks have the second highest natural radioactivity and contain fewer radioactive minerals. The natural radioactivity of sedimentary rocks mostly depends on their clay content. The gamma dose rate maps show that igneous and metamorphic regions around Raub have higher radioactivity compared to the sedimentary-dominated regions around Miri and Labuan. Annual effective dose (AED) and excess lifetime cancer risk (ELCR) were calculated to evaluate the potential health risk for inhabitants of these regions. Labuan and Miri are considered to be safe zones with respect to natural radioactivity as the results show little to no risk for the public, compared with the Raub region, which is medium to high risk.

Isolation and molecular detection of endophytic actinomycetes Nocardiopsis dassonvillei DMS 1 (MH900216) from marine sea grasses with bacterial inactivation - Chackaravarthi Gnanasekaran; Ramachandran Govindan; Mohan Kumar N.; Chenthis Kanisha Chelliah; Rajivgandhi Govindan; Priya Ranganathan; Maruthupandy Muthuchamy; Franck Quero; Arulraj Arunachalam; Mangalaraja Ramalinga Viswanathan; Naiyf S. Alharbi; Manoharan Natesan (Biocatalysis and Agricultural Biotechnology, 2023)

Concurrent Overexpression of Rice GS1;1 and GS2 Genes to Enhance the Nitrogen Use Efficiency (NUE) in Transgenic Rice - Shambhu Krishan Lal; Sahil Mehta; Dhandapani Raju; V. Mohan Murali Achary; Ajay Kumar Venkatapuram; Shashank Kumar Yadav; Hemangini Parmar; Rakesh Pandey; Varakumar Panditi; Vijay Sheri; Anil Kumar Singh; Viswanathan Chinnusamy; et al. (Journal of Plant Growth Regulation, 2023)

Spatiotemporal distribution of microplastics in Miri coastal area, NW Borneo: inference from a periodical observation - Anshuman Mishra; Prasanna Mohan Viswanathan; Nagarajan Ramasamy; Saravanan Panchatcharam; Chidambaram Sabarathinam (Environmental Science and Pollution Research, 2023)
The current study aims to investigate the spatiotemporal distribution of microplastics (MPs) in the Miri coast, targeting their occurrences, characterisation, and potential sources. For a periodical study, coastal sediments were collected from three different time intervals (monsoon, post-monsoon, and post-COVID) and subjected to stereomicroscope, ATR-FTIR, and SEM-EDX analyses. These results show a significant increase of MPs in post-COVID samples by approximately 218% and 148% comparatively with monsoon and post-monsoon samples, respectively. The highest concentration of MPs was detected near the river mouths and industrial areas where the waste discharge rate and anthropogenic activities dominate. Fibre-type MPs are the most abundant, with an average of nearly 64%, followed by fragments, films, microbeads, and foams. The most dominant polymer types were polytetrafluoroethylene (PTFE), polyethylene (PE), polypropylene (PP), polystyrene (PS), and polyester (PET). Overall, the current study shows a better understanding of MPs occurrence and potential sources in the Miri coastal area.

Distribution and fractionation of metals in tropical estuarine sediments, NW Borneo: Implication for ecological risk assessment - Rakesh Roshan Gantayat; Prasanna Mohan Viswanathan; Nagarajan Ramasamy; Chidambaram Sabarathinam (Journal of Geochemical Exploration, 2023)

Spatial and temporal variations of geochemical processes and toxicity of water, sediments, and suspended solids in Sibuti River Estuary, NW Borneo - Rakesh Roshan Gantayat; Prasanna Mohan Viswanathan; Nagarajan Ramasamy; Chidambaram Sabarathinam (Environmental Science and Pollution Research, 2023)
A comprehensive geochemical study was conducted in the Sibuti River estuary by considering water, suspended solids (SS), and sediment samples from 36 stations during southwest monsoon (SWM) and northeast monsoon (NEM). In this study, the distribution of in situ parameters, major ions, nutrients, trace metals, and isotopes (δD, δ 18 O) were analyzed in water samples, whereas sediments and SS were studied for trace metals. The distribution revealed that suspended solids were the major carrier of Cd, Zn, and Mn, whereas sediments worked as a major source of Co, Cr, Ba, Se, Cu, and Pb. Na-Cl water type and ion exchange dominated the lower part of the estuary during both seasons. However, the mixed mechanism of Ca–Cl, Ca–Mg–Cl, and higher weathering indicated reverse ion exchange in the intermediate and upper parts of the estuary. Isotopic signatures of δD and δ 18 O in estuarine water indicate that the precipitation over the Limbang area dominates during SWM, whereas higher evaporation was confirmed during NEM. The factor analysis revealed that seawater influence in the estuary majority controlled the water chemistry irrespective of seasons. Major ions were mainly regulated by the tidal influence during the low flow time of the river (SWM), whereas the mixing mechanism of weathering and seawater controlled the concentrations during NEM. Nutrients such as NO 3 , SO 4 2− , NH 3 , and NH 4 + mainly originated from the agricultural fields and nitrification along with ammonification were responsible for the recycling of such nutrients. Trace metals except Cd were found to be geogenic in nature and originating mainly from the oxidation of pyrites present in the sandstone and mudstones of the Sibuti Formation. Redox condition was catalyzed by microorganisms near the river mouth, whereas Al-oxyhydroxides and Fe-oxyhydroxides complexes in the intermediate and upper part under oxygenated conditions controlled the absorption of metals. Overall, the estuary was found to be absorptive in nature due to ideal pH conditions and was confirmed by the saturation index (SI) of minerals.

Occurrence and distribution of geochemical elements in Miri estuary, NW Borneo: Evaluating for processes, sources and pollution status - Parvin Raj Suresh Raj; Prasanna Mohan Viswanathan (Chemosphere, 2023)

Assessment on urban lakes along the coastal region of Miri, NW Borneo: implication for hydrochemistry, water quality, and pollution risk - Inez Neysa anak Nyambar; Prasanna Mohan Viswanathan (Environmental Science and Pollution Research, 2023)
The main purpose of this study is to assess the urban lake water quality along the coastal region of Miri City, Sarawak, East Malaysia. This study concentrates on the hydrochemical characteristics and the mechanisms controlling the suitability of the lakes for domestic, irrigation, and industrial purposes. A total of 15 lake water samples were collected and analysed for physical parameters, major ions, nutrients, BOD, COD, and heavy metals. The results show that Lakes 6, 7, and 8 commonly exceeded the National Drinking Water Quality Standards (NDWQS) limits, particularly in physical parameters and major ions. The cation dominance was Na + > Mg 2+ > K + > Ca 2+ , while the anion dominance was Cl − > HCO 3 − > SO 4 2− . It is inferred that lake 8 was affected by the seawater intrusion through the inlet flow, resulting in an excess concentration of ions present in that lake. The concentrations of heavy metals in these lakes were considerably low, indicating that most of them were from the geogenic source. Most of the lakes were NaCl water type and the main controlling mechanism were weathering and ionic exchange processes, with anthropogenic impacts. Based on the calculated Water Quality Index (WQI) according to the National Water Quality Standards (NWQS), all lakes were suitable for irrigation use (class IV), while most of these lakes fell under the “polluted” index. Apart from that, based on the National Lake Water Quality Standards (NLWQS), all lakes were classified under category D, indicating that the lakes must be kept in good condition. According to the irrigation quality indices, lakes 1, 2, 3, 4, and 5 were the most suitable for irrigation purposes. As for metal pollution indices (HPI and HEI), lakes 1, 2, 3, 4, 5, and 15 were considered safe with low pollution status. From the multivariate statistical analysis, it is deduced that both anthropogenic and geogenic impacts mostly influenced the quality of these lake waters. The outcome of this study will help the policymakers under the national water department in sustainable management of water resources in this region.

SARS-CoV-2 phase I transmission and mutability linked to the interplay of climatic variables: a global observation on the pandemic spread - Chidambaram Sabarathinam; Prasanna Mohan Viswanathan; Venkatramanan Senapathi; Shankar Karuppannan; Dhanu Radha Samayamanthula; Gnanachandrasamy Gopalakrishnan; Ramanathan Alagappan; Prosun Bhattacharya (Environmental Science and Pollution Research, 2022)

Determination of vulnerable regions of SARS-CoV-2 in Malaysia using meteorology and air quality data - Prasanna Mohan Viswanathan; Chidambaram Sabarathinam; Shankar Karuppannan; Gnanachandrasamy Gopalakrishnan (Environment, Development and Sustainability, 2022)

Mechanism underpinning the sharpening of orientation and spatial frequency selectivities in the tree shrew (Tupaia belangeri) primary visual cortex - Yamni S. Mohan; Sivaram Viswanathan; Jaikishan Jayakumar; Errol K. J. Lloyd; Trichur R. Vidyasagar (Brain Structure and Function, 2022)

A study on geochemistry and sources of colloidal fractions in coastal groundwater from different lithologies - Pradeep Kamaraj; Chidambaram Sabarathinam; H Seshadri; Banajarani Panda; Brindha Karthikeyan; Prasanna Mohan Viswanathan; Ramesh Govindaraj; Ganesh Nagappan (Journal of Earth System Science, 2022)

Delineating saline and fresh water aquifers in Tuticorin of southern India by using geophysical techniques - Selvam Sekar; Jesuraja Kamaraj; Venkatramanan Senapathi; Chidambaram Sabarathinam; Prasanna Mohan Viswanathan; Sivakumar Karthikeyan (Environment, Development and Sustainability, 2021)

Biofilm inhibition and antifouling evaluation of sol-gel coated silicone implants with prolonged release of eugenol against Pseudomonas aeruginosa - Prasanth Rathinam; Bhasker Mohan Murari; Pragasam Viswanathan (Biofouling, 2021)

Glycemic index of pulses and pulse-based products: a review - Maleeka Singh; Annamalai Manickavasagan; Shanmugam Shobana; Viswanathan Mohan (Critical Reviews in Food Science and Nutrition, 2021)

Augmentation of RBP4/STRA6 signaling leads to insulin resistance and inflammation and the plausible therapeutic role of vildagliptin and metformin - Kuppan Gokulakrishnan; Gautam Kumar Pandey; Chandrakumar Sathishkumar; Saravanakumar Sundararajan; Prabhu Durairaj; Nagaraj Manickam; Viswanathan Mohan; Muthuswamy Balasubramanyam (Molecular Biology Reports, 2021)

Recent environmental geochemical trends in water and sediments—a framework on OSPRC - Venkatramanan Senapathi; Selvam Sekar; Prasanna Mohan Viswanathan (Environmental Science and Pollution Research, 2021)

A comparative study on the cellular stressors in mesenchymal stem cells (MSCs) and pancreatic β-cells under hyperglycemic milieu - Srividhya Raghavan; Sarubala Malayaperumal; Viswanathan Mohan; Muthuswamy Balasubramanyam (Molecular and Cellular Biochemistry, 2021)

Health Risk Implication and Spatial Distribution of Radon in Groundwater Along the Lithological Contact in South India - Vasanthakumari Sivasankara Pillai Adithya; Sabarathinam Chidambaram; Mohan Viswanathan Prasanna; Senapathi Venkatramanan; Keesari Tirumalesh; Chandrasekar Thivya; Rajendiran Thilagavathi (Archives of Environmental Contamination and Toxicology, 2021)

Occurrence of Heavy Metals in Groundwater Along the Lithological Interface of K/T Boundary, Peninsular India: A Special Focus on Source, Geochemical Mobility and Health Risk - Thivya Chandrasekar; Tirumalesh Keesari; Gnanachandrasamy Gopalakrishnan; Shankar Karuppannan; Venkatramanan Senapathi; Chidambaram Sabarathinam; Prasanna Mohan Viswanathan (Archives of Environmental Contamination and Toxicology, 2021)

Identification of groundwater potential zones using geospatial approach in Sivagangai district, South India - Agastheeswaran Vellaikannu; Udayaganesan Palaniraj; Sivakumar Karthikeyan; Venkatramanan Senapathi; Prasanna Mohan Viswanathan; Selvam Sekar (Arabian Journal of Geosciences, 2021)

Chemical characteristics of rainwater in the tropical rainforest region in northwestern Borneo - Ninu Krishnan Modon Valappil; Prasanna Mohan Viswanathan; Vijith Hamza (Environmental Science and Pollution Research, 2020)

Seasonal hydrochemical dynamics of surface water in the Limbang River, Northern Borneo—evaluating for spatial and temporal trends - Ninu Krishnan Modon Valappil; Prasanna Mohan Viswanathan; Vijith Hamza (Arabian Journal of Geosciences, 2020)

Seasonal changes in groundwater quality deterioration and chemometric analysis of pollution source identification in South India - Adithya Vasanthakumari Sivasankara Pillai; Chidambaram Sabarathinam; Tirumalesh Keesari; Thivya Chandrasekar; Thilagavathi Rajendiran; Venkatramanan Senapathi; Prasanna Mohan Viswanathan; Dhanu Radha Samayamanthu (Environmental Science and Pollution Research, 2020)

Correction to: Prevalence and correlates of household food insecurity in Delhi and Chennai, India - Garima Rautela; Mohammed K. Ali; Dorairaj Prabhakaran; K.M. Venkat Narayan; Nikhil Tandon; Viswanathan Mohan; Lindsay M. Jaacks (Food Security, 2020)

Prevalence and correlates of household food insecurity in Delhi and Chennai, India - Garima Rautela; Mohammed K. Ali; Dorairaj Prabhakaran; K.M. Venkat Narayan; Nikhil Tandon; Viswanathan Mohan; Lindsay M. Jaacks (Food Security, 2020)

Influence of variations in rainfall pattern on the hydrogeochemistry of coastal groundwater—an outcome of periodic observation - Thilagavathi Rajendiran; Chidambaram Sabarathinam; Thivya Chandrasekar; Tirumalesh Keesari; Venkatramanan Senapathi; Pethaperumal Sivaraman; Prasanna Mohan Viswanathan; Ganesh Nagappan (Environmental Science and Pollution Research, 2019)

Novel insights of elevated systemic levels of bisphenol-A (BPA) linked to poor glycemic control, accelerated cellular senescence and insulin resistance in patients with type 2 diabetes - Avinash Soundararajan; Paramasivam Prabu; Viswanathan Mohan; Yann Gibert; Muthuswamy Balasubramanyam (Molecular and Cellular Biochemistry, 2019)

Phytochemical constituents from dietary plant Citrus hystrix - Mathusalini Sadasivam; Chandraprakash Kumarasamy; Arasakumar Thangaraj; Mani Govindan; Gayathri Kasirajan; Viswanathan Vijayan; Velmurugan Devadasan; Lin Chia-Her; Gogul Ramnath Madhusudhanan; Thirugnanasampandan Ramaraj; Mohan Palathurai Subramaniam (Natural Product Research, 2018)

Association of recently identified type 2 diabetes gene variants with Gestational Diabetes in Asian Indian population - Sekar Kanthimathi; Manickam Chidambaram; Dhanasekaran Bodhini; Samuel Liju; Aruyerchelvan Bhavatharini; Ram Uma; Ranjit Mohan Anjana; Viswanathan Mohan; Venkatesan Radha (Molecular Genetics and Genomics, 2017)

SEAP activity serves for demonstrating ER stress induction by glucolipotoxicity as well as testing ER stress inhibitory potential of therapeutic agents - Raji Lenin; Viswanathan Mohan; Muthuswamy Balasubramanyam (Molecular and Cellular Biochemistry, 2015)

Accelerated fat cell aging links oxidative stress and insulin resistance in adipocytes - Finny Monickaraj; Sankaramoorthy Aravind; Pichamoorthy Nandhini; Paramasivam Prabu; Chandrakumar Sathishkumar; Viswanathan Mohan; Muthuswamy Balasubramanyam (Journal of Biosciences, 2013)

ACACβ gene (rs2268388) and AGTR1 gene (rs5186) polymorphism and the risk of nephropathy in Asian Indian patients with type 2 diabetes - Viral N. Shah; Balneek Singh Cheema; Rajni Sharma; Madhu Khullar; Harbir Singh Kohli; Tarunveer Singh Ahluwalia; Viswanathan Mohan; Anil Bhansali (Molecular and Cellular Biochemistry, 2013)

Hyperinsulinemia-induced vascular smooth muscle cell (VSMC) migration and proliferation is mediated by converging mechanisms of mitochondrial dysfunction and oxidative stress - Shiny Abhijit; Regin Bhaskaran; Abirami Narayanasamy; Anand Chakroborty; Nagaraj Manickam; Madhulika Dixit; Viswanathan Mohan; Muthuswamy Balasubramanyam (Molecular and Cellular Biochemistry, 2013)

Accelerated aging as evidenced by increased telomere shortening and mitochondrial DNA depletion in patients with type 2 diabetes - Finny Monickaraj; Sankaramoorthy Aravind; Kuppan Gokulakrishnan; Chandrakumar Sathishkumar; Paramasivam Prabu; Durai Prabu; Viswanathan Mohan; Muthuswamy Balasubramanyam (Molecular and Cellular Biochemistry, 2012)

Lack of association of PTPN1 gene polymorphisms with type 2 diabetes in south Indians - DHANASEKARAN BODHINI; VENKATESAN RADHA; SAURABH GHOSH; PARTHA P. MAJUMDER; VISWANATHAN MOHAN (Journal of Genetics, 2011)

Study of evaluation of groundwater in Gadilam basin using hydrogeochemical and isotope data - Mohan Viswanathan Prasanna; S. Chidambaram; A. Shahul Hameed; K. Srinivasamoorthy (Environmental Monitoring and Assessment, 2010)

Subclinical inflammation/oxidation as revealed by altered gene expression profiles in subjects with impaired glucose tolerance and Type 2 diabetes patients - Kuppan Gokulakrishnan; Kutuva Tulasi Mohanavalli; Finny Monickaraj; Viswanathan Mohan; Muthuswamy Balasubramanyam (Molecular and Cellular Biochemistry, 2009)

A novel association of a polymorphism in the first intron of adiponectin gene with type 2 diabetes, obesity and hypoadiponectinemia in Asian Indians - Karani S. Vimaleswaran; Venkatesan Radha; Kandaswamy Ramya; Hunsur Narayan Sathish Babu; Nageshappa Savitha; Venkataramaiah Roopa; Dhar Monalisa; Raj Deepa; Saurabh Ghosh; Partha P. Majumder; M. R. Sathyanarayana Rao; Viswanathan Mohan (Human Genetics, 2008)

Association of hypoglutathionemia with reduced Na+/K+ ATPase activity in type 2 diabetes and microangiopathy - Rangasamy Sampathkumar; Muthuswamy Balasubramanyam; Cherian Tara; Mohan Rema; Viswanathan Mohan (Molecular and Cellular Biochemistry, 2006)

Is insulin signaling molecules misguided in diabetes for ubiquitin–proteasome mediated degradation? - Muthuswamy Balasubramanyam; Rangasamy Sampathkumar; Viswanathan Mohan (Molecular and Cellular Biochemistry, 2005)